Promising bioactive properties of quercetin for potential food applications and health benefits: A review - Shabir, Irtiqa; Kumar Pandey, Vinay; Shams, Rafeeya; Dar, Aamir Hussain; Dash, Kshirod Kumar; Khan, Shafat Ahmad; Bashir, Iqra; Jeevarathinam, G.; Rusu, Alexandru Vasile; Esatbeyoglu, Tuba; Pandiselvam, R. (Frontiers in Nutrition, 2022)
Naturally occurring phytochemicals with promising biological properties are quercetin and its derivatives. Quercetin has been thoroughly studied for its antidiabetic, antibacterial, anti-inflammatory, anti- Alzheimer's, anti-arthritic, antioxidant, cardiovascular, and wound-healing properties. Anticancer activity of quercetin against cancer cell lines has also recently been revealed. The majority of the Western diet contains quercetin and its derivatives, therefore consuming them as part of a meal or as a food supplement may be sufficient for people to take advantage of their preventive effects. Bioavailability-based drug-delivery systems of quercetin have been heavily studied. Fruits, seeds, vegetables, bracken fern, coffee, tea, and other plants all contain quercetin, as do natural colours. One naturally occurring antioxidant is quercetin, whose anticancer effects have been discussed in detail. It has several properties that could make it an effective anti-cancer agent. Numerous researches have shown that quercetin plays a substantial part in the suppression of cancer cells in the breast, colon, prostate, ovary, endometrial, and lung tumours. The current study includes a concise explanation of quercetin's action mechanism and potential health applications.